Respon Imun Ikan Nila (Oreochromis niloticus) Yang Terinfeksi Bakteri (Aeromonas hydrophila) Dengan Penambahan Vitamin C Pada Pakan - Pebriani, Dewa Ayu Angga; Wijayanti, Ni Putu Putri; Sudaryatma, Putu Eka; Octovianus, Octovianus (Journal of Marine and Aquatic Sciences, 2022)
Tilapia ( Oreochromis niloticus ) is one of the freshwater fish commodities with important economic value. However, in tilapia aquaculture, the emergence of disease was one of the problems that affect the quality and quantity of aquaculture production. One of the diseases that often appears was infection with Aeromonas hydrop hila bacteria. This problem is expected to be overcome by giving vitamin C in fish feed. Through the provision of vitamin C, it will be able to increase the fish's immune system which is directly related to the fish's ability to prevent or treat disease attacks that arise, especially from Aeromonas hydro phila bacteria. The aim of this study was to determine the response of vitamin C to the immune system of fish infected with Aeromonas hydrop hila so that the best dose was known that could be applied in the treatment of Aeromonas hydrophyla bacteria attack. The study was conducted using an experimental method with a completely randomized design (CRD) consisted of 2 controls, namely positive control and negative control, and 3 treatments with different doses of vitamin C. Based on the hematological test, the results showed that the content of white blood cells, red blood cells, and hemoglobin were still in the normal range for all treatments. Treatment E with a dose of 450 mg/kg vitamin C was able to increase the immune system of tilapia infected with Aeromonas hydrop hila bacteria, shown from the content of white blood cells, red blood cells and hemoglobin in the highest treatment E compared to other treatments.